Membuat kalimat efektif dan memperbaiki kalimat tidak efektif - zada, ahmad lucky hamami (Maliki Interdisciplinary Journal, 2026)
This article addresses the crucial skill of constructing effective sentences and correcting inaccurate ones in writing, particularly in an academic setting. Effective sentences are essential because they ensure the intended message is clear, precise, and immediately understandable to the reader, thus preventing misinterpretation.We detail the core concept and key characteristics of effective sentences. A strong sentence must possess a complete structure (subject and predicate) , be economical in its wording (avoiding redundancy) , be logical, and be free from double meanings (ambiguity). Furthermore, the discussion offers practical steps for correcting ineffective writing : simplifying overly complex structures , replacing inappropriate word choices (diction) , and ensuring adherence to standard language rules, including correct spelling and punctuation. The ultimate goal is to help readers enhance their written communication to be clearer and more professional.